2000
DOI: 10.1073/pnas.97.8.4180
|View full text |Cite
|
Sign up to set email alerts
|

Sox6is a candidate gene forp100Hmyopathy, heart block, and sudden neonatal death

Abstract: The mouse p locus encodes a gene that functions in normal pigmentation. We have characterized a radiation-induced mutant allele of the mouse p locus that is associated with a failure-to-thrive syndrome, in addition to diminished pigmentation. Mice homozygous for this mutant allele, p 100H , show delayed growth and die within 2 wk after birth. We have discovered that the mutant mice develop progressive atrioventricular heart block and significant ultrastructural changes in both cardiac and skeletal muscle cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
96
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 36 publications
(44 reference statements)
0
96
0
Order By: Relevance
“…This suggestion can explain the postnatal lethal phenotype of homozygote mutant mice where a chromosomal inversion affects the Sox6 gene (29) and of mice with a targeted mutation of both Sox6 alleles (30). The striking finding that SRY can complement splicing activity of a nuclear extract that has been depleted of SOX6 indicates a role in splicing also for the testis-determining factor.…”
Section: Discussionmentioning
confidence: 95%
“…This suggestion can explain the postnatal lethal phenotype of homozygote mutant mice where a chromosomal inversion affects the Sox6 gene (29) and of mice with a targeted mutation of both Sox6 alleles (30). The striking finding that SRY can complement splicing activity of a nuclear extract that has been depleted of SOX6 indicates a role in splicing also for the testis-determining factor.…”
Section: Discussionmentioning
confidence: 95%
“…Two major size classes of SOX6 transcripts in mouse (Hagiwara et al, 2000), rat (Narahara et al, 2002), and human (Cohen-Barak et al, 2001) have been demonstrated: a small transcript of about 3 kb and a large one of 8-9 kb. The size difference is thought to be owing to the different sizes of the 3 0 and 5 0 UTRs (Lefebvre et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The SOX6 gene showed significantly higher expression in all the glioma tissues analysed than in the normal adult brain ( Figure 3b). The large and small transcripts of SOX6 have been reported in mouse (Lefebvre et al, 1998;Hagiwara et al, 2000) and human (Cohen-Barak et al, 2001), and the size difference is most likely owing to the different sizes of the 3 0 and 5 0 untranslated regions (UTRs) (Lefebvre et al, 1998). The small transcript is predominantly expressed in the adult mouse testis and the large one is expressed in the developing mouse brain and mouse chondrocytes, but the expression significantly decreases in these adult tissues (Connor et al, 1995;Lefebvre et al, 1998).…”
Section: Analysis Of Sox6 Gene Expression In Gliomamentioning
confidence: 99%
“…The short form mSox6 was expressed predominantly in neonatal brain and adult testis. 32) By contrast, the long form mSox6 was most abundantly expressed in skeletal muscle, although it was expressed at varied levels in the other tissues such as heart, spleen, liver, and kidney of adult mouse. 32) In this study, rSox6 expression could not be detected in the organs except neonatal brain, adult testis, whole eye and ovary.…”
Section: Fig 2 Nucleotide Sequence Of Rsox6 Cdna and Comparison Ofmentioning
confidence: 94%
“…24) Since these motifs of Sox6 were conserved in the rSox6, rSox6 was suggested to have the same function as that of the reported Sox6. 24,26,[32][33][34] Organ Distributions of the rSox6 Gene Mouse Sox6 was reported to be expressed in neonatal brain and adult testis.…”
Section: Fig 2 Nucleotide Sequence Of Rsox6 Cdna and Comparison Ofmentioning
confidence: 99%